1982
DOI: 10.1042/bj2010267
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of smooth-muscle myosin by trypsin-like serine proteinases.

Abstract: 1. Hydrolysis of the myosins from smooth and from skeletal muscle by a rat trypsin-like serine proteinase and by bovine trypsin at pH 7 is compared. 2. Proteolysis of the heavy chains of both myosins by the rat enzyme proceeds at rates approx. 20 times faster than those obtained with bovine trypsin. Whereas cleavage of skeletal-muscle myosin heavy chain by both enzymes results in the generation of conventional products i.e. heavy meromyosin and light meromyosin, the heavy chain of smooth-muscle myosin is degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…Although, according to the reports of Kay et al. a certain intracellular serine protease mainly participates in initial degradation of myofibrillar proteins in mouse muscle, 1,2 only a few studies have been reported on intracellular serine protease in fish muscle. According to the previous studies, fish muscle serine proteases are roughly divided into two groups on the basis of the behavior of solubility in muscle homogenate.…”
Section: Effect Of Various Protease Inhibitors On the Activity Of Thmentioning
confidence: 98%
“…Although, according to the reports of Kay et al. a certain intracellular serine protease mainly participates in initial degradation of myofibrillar proteins in mouse muscle, 1,2 only a few studies have been reported on intracellular serine protease in fish muscle. According to the previous studies, fish muscle serine proteases are roughly divided into two groups on the basis of the behavior of solubility in muscle homogenate.…”
Section: Effect Of Various Protease Inhibitors On the Activity Of Thmentioning
confidence: 98%
“…For the nonlysosomal pathway, three protein degradation systems are involved, including the ubiquitin-proteasome system (2), the calpain-µ and -m system (3), and a serine proteinase system (4)(5)(6). Concerning the serine proteinase system, the involvement of a myofibril-bound serine proteinase (MBSP) is noteworthy.…”
Section: Introductionmentioning
confidence: 99%
“…2000). Except calpains (Mykles and Skinner 1983), proteinases involved in the nonlysosomal pathway have been characterized as serine proteinases (Kay et al. 1982a,b).…”
Section: Introductionmentioning
confidence: 99%